Estrogenic mycotoxins in surface waters of the rico stream micro-basin, SãO Paulo, Brazil: Occurrence and potential estrogenic contribution - Emídio, Elissandro Soares [UNESP] (2020)
The aim of this study was to assess the occurrence of zearalenone (ZEN) and its metabolites zearalanone (ZAN), α-zearalenol (α-ZEL), β-zearalenol (β-ZEL) α-zearalanol (α-ZAL), and β-zearalanol (β-ZAL) in the surface waters of northern Sao Paulo state (Brazil) and to evaluate the associated potential estrogenic contribution to the aquatic environment. The determination of the estrogenic mycotoxins in water samples from the Rico Stream microbasin yielded levels of up to 59 ng L-1 and their corresponding calculated estrogenic equivalent (cEEQ) values were between < 0.03 and 1.4 ng L-1, which are associated with negative effects on the reproduction and growth of some fish species. The physicochemical and microbiological parameters were evaluated to determine the water quality in the Rico stream region. This study revealed the first data about the presence of estrogenic mycotoxins in the Brazilian river waters and emphasizes the need to include these substances in future public policies concerning water quality, since these compounds are not yet legally regulated. From an environmental aspect, it is necessary to take into account the continuous introduction into surface water of microcontaminants associated with wastewater effluent, such as estrogenic mycotoxins.